Study on cellulose microfilaments based composite spheres: Microwave-assisted synthesis, characterization, and application in pollutant removal. (15th December 2018) - Li, Yuan; Xiao, Huining; Pan, Yuanfeng; Zhang, Min; Ni, Shuzhen; Hou, Xiaobang; Hu, Erfeng
Abstract: A novel study of synthesizing the temperature-responsive polymer grafted cellulose filaments/Poly (N-isopropylacrylamide) (NIPAM) spheres (P-MCCBs) was carried out for the removal of dyes and heavy metal ions. The novelty of the presented work consists of the application of the nano-sized pore-forming agent (Calcium Carbonate) and the introduction of a temperature-responsive monomer (NIPAM) while preparing the adsorbents. In addition, the spherical adsorbents were synthesized through an in-situ free radical polymerization using a microwave-assisted heating approach. The morphology, chemical structure, pH, and thermal sensitivity of P-MCCBs were characterized properly. The adsorption and desorption behaviors of dyes and heavy metal ions on P-MCCBs were also investigated. The results showed that P-MCCBs exhibited a fast adsorption rate, the adsorption equilibrium reached within 80 min and 40 min for MB and Pb 2+, respectively (25 °C). Moreover, around 5–8% and 20% of adsorbed MB and Pb 2+ were released at the temperature above 45 °C. The adsorption kinetics followed pseudo-second-order model, and the desorption process was fit well using Higuchi and Korsmeyer-Peppas models. These results indicated that P-MCCBs could be served as a novel material for controllable adsorption and desorption processes of various contaminants. Graphical abstract: Highlights: A novel study on temperature-responsive cellulose filaments spheres (P-MCCBs). P-MCCBs exhibited the temperature sensitivity on contaminants adsorption. A controllable desorption process of methylene blue and Pb 2+ was observed. The mechanism of the desorption process was studied using various kinetics models. P-MCCBs is a sustainable renewable bio-adsorbent for effluent treatment.